Imaging of perfusion, angiogenesis, and tissue elasticity after stroke - Martín, Abraham (Nature Publishing Group, 2012)
Blood flow interruption in a cerebral artery causes brain ischemia and induces dramatic changes of perfusion and metabolism in the corresponding territory. We performed in parallel positron emission tomography (PET) with [(15)O]H(2)O, single photon emission computed tomography (SPECT) with [(99m)Tc]hexamethylpropylene-amino-oxime ([(99m)Tc]HMPAO) and ultrasonic ultrafast shear wave imaging (SWI) during, immediately after, and 1, 2, 4, and 7 days after middle cerebral artery occlusion (MCAO) in rats. Positron emission tomography and SPECT showed initial hypoperfusion followed by recovery at immediate reperfusion, hypoperfusion at day 1, and hyperperfusion at days 4 to 7. Hyperperfusion interested the whole brain, including nonischemic areas. Immunohistochemical analysis indicated active angiogenesis at days 2 to 7, strongly suggestive that hyperperfusion was supported by an increase in microvessel density in both brain hemispheres after ischemia. The SWI detected elastic changes of cerebral tissue in the ischemic area as early as day 1 after MCAO appearing as a softening of cerebral tissue whose local internal elasticity decreased continuously from day 1 to 7. Taken together, these results suggest that hyperperfusion after cerebral ischemia is due to formation of neovessels, and indicate that brain softening is an early and continuous process. The SWI is a promising novel imaging method for monitoring the evolution of cerebral ischemia over time in animals.